2008
DOI: 10.1186/1465-9921-9-16
|View full text |Cite
|
Sign up to set email alerts
|

Nontypeable Haemophilus influenzae induces COX-2 and PGE2 expression in lung epithelial cells via activation of p38 MAPK and NF-kappa B

Abstract: Background: Nontypeable Haemophilus influenzae (NTHi) is an important respiratory pathogen implicated as an infectious trigger in chronic obstructive pulmonary disease, but its molecular interaction with human lung epithelial cells remains unclear. Herein, we tested that the hypothesis that NTHi induces the expression of cyclooxygenase (COX)-2 and prostaglandin E2 (PGE2) via activation of p38 mitogen-activated protein kinase (MAPK) and nuclear factor (NF)-kappa B in pulmonary alveolar epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…Multiple studies demonstrated the utility of NTHi lysate in elucidating the pathogenesis and host response to bacterial infection (6,15,(17)(18)(19)(20)(21)(22)(23). Therefore, we initially determined whether NTHi lysate induces an in vitro inflammatory response in A549 cells, a human lung epithelial cell line that is commonly used to study airway inflammation.…”
Section: Nthi Lysate Increases the Release Of Il-8 And Cellular Concementioning
confidence: 99%
“…Multiple studies demonstrated the utility of NTHi lysate in elucidating the pathogenesis and host response to bacterial infection (6,15,(17)(18)(19)(20)(21)(22)(23). Therefore, we initially determined whether NTHi lysate induces an in vitro inflammatory response in A549 cells, a human lung epithelial cell line that is commonly used to study airway inflammation.…”
Section: Nthi Lysate Increases the Release Of Il-8 And Cellular Concementioning
confidence: 99%
“…Activation of toll-like receptors may similarly stimulate the formation of PGE 2 [45][46][47]. Hitherto an effect of Pam3CSK4 on prostaglandin formation has, however, not been shown.…”
Section: Discussionmentioning
confidence: 99%
“…p38 MAPK regulates PGE 2 synthesis in nonmacrophage cells, including lung epithelial cells infected with Haemophilus influenzae (18). F. tularensis stimulates the phosphorylation and activation of p38 MAPK following infection of macrophages (19).…”
Section: Resultsmentioning
confidence: 99%